Chlorine Atom Transfer Radical 6‐exo Cyclizations of Carbamoyldichloroacetate‐Tethered Alkenes, Enol Acetates and α, β‐Unsaturated Nitriles Leading to Morphans. Issue 11 (6th February 2014) - Diaba, Faïza; Martínez‐Laporta, Agustín; Bonjoch, Josep
Abstract: The Cu I ‐mediated atom transfer radical cyclization of amino‐tethered dichloromalonamides and electron‐rich, electron‐poor, and nonactivated double bonds is a useful methodology for the synthesis of 2‐azabicyclo[3.3.1]nonanes. A study of the reaction conditions and the scope of the process is reported. Cyclopropane ring formation was observed from the resulting 1, 3‐dichlorides in some morphan substrates using either Cu I, Pd, or Zn. Abstract : Synthetic studies have shown that radical species with electron‐withdrawing groups undergo cyclization processes leading to morphan compounds irrespective of the nature of the radical acceptor. Since the intramolecular addition products are 1, 3‐dichlorides, under some conditions an additional dehalogenation step was observed, leading to cyclopropanes embedded in the morphan nucleus.